Make-or-buy configurational approaches in product-service ecosystems and performance - Bustinza, Oscar F.; Lafuente, Esteban; Rabetino, Rodrigo; Vaillant, Yancy; Vendrell-Herrero, Ferran (Elsevier, 2019)
This research examines firm boundary configurations for manufacturers' product-service offerings. We argue that the building of a product-service ecosystem through collaboration with service providers in certain types of business services can increase performance as a result of the superior knowledge-based resources coming from specialized partners. By using fuzzy set qualitative analysis on a sample of 370 multinational manufacturing enterprises (MMNEs), the results reveal that effective servitization is heterogeneous across manufacturing industries and across business service offerings. The findings indicate that most industries achieve their highest performance through collaborations with value-added service providers in two out of three of the service continuum stages (Base and Intermediate services); while keeping the development of Advanced services in-house. The results help to contextualize the best practices for implementing service business models in MMNEs by detailing which service capabilities should be retained in-house and which should be outsourced to specialized partners in various industrial contexts.
Keywords: servitization; ecosystems; make-or-buy; knowledge-intensive business service firms; product-service systems; fi=Johtaminen ja organisaatiot|en=Management and Organization|